Unit Root Analysis Method of Actual Crack Behavior of the Concrete Dam Based on Residuals of the Monitoring Model - Bo Xu; Zhanchao Li; Jinlei Zhao (Advances in Civil Engineering)
Analysis on the actual crack behavior is of important significance to evaluate safety of the concrete dam. In this paper, mainly based on the research status on cracks of the concrete dam, the unit root analysis method of actual crack behavior of concrete dam is proposed based on the monitoring data and autoregression model, aiming to enrich the analysis methods of crack behavior of concrete dam and deepen the understanding of crack behavior of concrete dam. Firstly, the feasibility of analyzing actual crack behavior based on residual sequence of the crack opening displacement monitoring model is discussed. Next, the basic principle of the unit root analysis method of crack behavior is elaborated and the unit root analysis method of actual crack behavior is established by studying prior conditions of the autoregression model and parameter estimation methods of the autoregression model, as well as determination criteria of the model order. Finally, the proposed unit root analysis method of actual crack behavior is applied to analyze monitoring data of a concrete gravity-arch dam. The result shows that the unit root analysis method of actual crack behavior is relatively simple and convenient in practical application, which is an available method to evaluate crack behavior based on data in dam health monitoring.